2006
DOI: 10.5367/000000006776387150
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Cost Efficiency of International Tourist Hotels in Taiwan

Abstract: This study employs data envelopment analysis (DEA) to evaluate the relative cost efficiency of 49 international tourist hotels in Taiwan. The study uses five different measures: overall efficiency (OE), allocative efficiency (AE), technical efficiency (TE), scale efficiency (SE) and pure technical efficiency (PTE). Applying efficiency measures derived from the DEA estimation, hotel efficiency determinants are evaluated using the Tobit regression model. A bootstrapping technique is applied to overcome the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 48 publications
5
80
1
5
Order By: Relevance
“…Productivity is always a top priority for hotel operators (Brown & Dev, 1999Reynolds & Thompson, 2007;Sigala, 2004;Wang, Hung, & Shang, 2006). Hotel productivity generally encompasses an umbrella concept that includes efficiency, effectiveness, quality, predictability, and other performance dimensions, as well as a concept reflecting only production efficiency (Sigala).…”
Section: Hotel Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Productivity is always a top priority for hotel operators (Brown & Dev, 1999Reynolds & Thompson, 2007;Sigala, 2004;Wang, Hung, & Shang, 2006). Hotel productivity generally encompasses an umbrella concept that includes efficiency, effectiveness, quality, predictability, and other performance dimensions, as well as a concept reflecting only production efficiency (Sigala).…”
Section: Hotel Productivitymentioning
confidence: 99%
“…A major advantage of DEA is that it does not require an assumption about the functional form of the model that underpins the relationships between the input and output variables (Hwang & Chang, 2003). Wang et al (2006) employed the DEA and used the Tobit regression model to evaluate the efficiency determinants of the firms. This model was applied because firm and market factors can be differentiated and are beyond the traditional input-output setting, but contribute to efficiency.…”
Section: Productivity Assessment Using Data Envelopment Analysismentioning
confidence: 99%
“…This study also found that the relative efficiency of those ITHs located in scenic areas is higher than those in cities. Hung et al (2006) studied the relative efficiency of ITHs in Taiwan, using five different measures: overall efficiency (OE), allocative efficiency (AE), technical efficiency (TE), scale efficiency (SE), and pure technical efficiency (PTE). The result indicated these ITHs in Taiwan are inefficient.…”
Section: Dea Approachmentioning
confidence: 99%
“…The Taiwan Assessment and Evaluation Association has been delegated to conduct the rating. So far, most related literature has been focused on the levels and differences of operational efficiency of chain hotels and independent hotels (Hwang & Chang, 2003;Wang, Hung, & Shang, 2006;Chiang, Tsai, & Wang, 2004). Nevertheless, what hotels are facing is a highly competitive market, especially five-star hotels that are dedicated to serving customers of higher socio-economic demographics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the difference in the performance of these hotels was significantly related to whether the guests were foreigners and the management style of the hotel (independent or affiliated to an international chain). Wang et al (2006) conducted a study on the operational efficiency of international hotels in Taiwan and discovered that the average efficiency was 0.81, failing to achieve the relative operational efficiency standard and indicating that the hotels could reduce 19% of their personnel, number of rooms or the floor area of their food and beverage departments to make improvements. The results obtained through Tobit regression showed that those targeting the business hotel market faced tougher competition whereas the ones affiliated to hotel chains (as opposed to those independently managed) had better efficiency and scale had no significant influence.…”
Section: Literature Reviewmentioning
confidence: 99%